2012
DOI: 10.4103/0972-6748.110955
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine responsive catatonia: A series of five cases

Abstract: The main objective of presenting the case series is that despite dramatic symptomatic response by intra venous lorazepam or electro convulsive therapy irrespective of primary diagnosis in catatonia cases some cases remain difficult to treat by conventional treatment. Here, we present five catatonia cases who did not respond to conventional treatment even when treated for primary psychiatric diagnosis along with treatment for catatonia. They ultimately responded partially or completely to clozapine only, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 15 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Valevski et al [ 11 ] described two patients who responded well to risperidone. There are multiple positive reports on the treatment of catatonia with clozapine, but due to the slow introduction and close monitoring required with clozapine this may only be an option limited to chronic, severe, and treatment-resistant cases [ 12 – 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Valevski et al [ 11 ] described two patients who responded well to risperidone. There are multiple positive reports on the treatment of catatonia with clozapine, but due to the slow introduction and close monitoring required with clozapine this may only be an option limited to chronic, severe, and treatment-resistant cases [ 12 – 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coming to the management, Clozapine is recommended for management of TD [2]. Literature also supports efficacy of Clozapine in catatonia [4,8]. The stronger D1 binding and rapid dissociation from D2 receptors can explain its efficacy in both the disorders [2].…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] In line with the usual recommendation for clozapine initiation, the treatment requires a baseline evaluation, slow titration and close monitoring. 10 A daily dose between 300 and 750 mg may be required to achieve efficacy, 10,11 and relief from catatonic symptoms is observed within 2-7 weeks of treatment. [10][11][12] The neurobiology of catatonia is complex, [13][14][15] and clozapine may be effective through its actions at various biological junctures of this neurobiology.…”
mentioning
confidence: 99%
“…3,4 Even though NMS was described in some catatonic patients treated with clozapine, 8 this medication has been shown to be more efficient than other APs for the treatment of chronic catatonia with schizophrenia, although most of the studies reported on a small number of cases. [10][11][12] In line with the usual recommendation for clozapine initiation, the treatment requires a baseline evaluation, slow titration and close monitoring.10 A daily dose between 300 and 750 mg may be required to achieve efficacy, 10,11 and relief from catatonic symptoms is observed within 2-7 weeks of treatment. …”
mentioning
confidence: 99%
See 1 more Smart Citation